Illegal Logging and Endangered Animals: The urgency of Establishing Independent Institutions in Environmental Management and Protection - Sulistianingsih, Dewi; Prasetyo Adhi, Yuli; Ilmiyah, Nofika; Martitah, Martitah; Mohd Yusoff, Rahmawati (Indonesian Journal of Environmental Law and Sustainable Development, 2025)
This paper aims to analyse the urgency of establishing independent institutions in environmental management and protection in Indonesia, especially in dealing with illegal logging and the preservation of endangered animal habitats. Using normative juridical methods as well as conceptual and comparative approaches, this study highlights the weaknesses of the OSS-RBA-based licensing system as well as the weak law enforcement against the exploitation of natural resources. The results of the study show that gaps in the licensing system open opportunities for illegal logging practices that increasingly threaten the sustainability of the ecosystem and cause a decline in the population of endangered animals. Compared to other developed countries, Indonesia does not yet have an independent institution specifically supervising licensing and law enforcement in the environmental sector. This study confirms that policies in Brazil can provide a deterrent effect for illegal logging perpetrators by applying strict sanctions in the form of large fines, asset confiscation, and prison sentences of up to 10 years. The establishment of independent institutions in Indonesia is urgently needed to ensure strict supervision and the application of strict sanctions to protect ecosystems and prevent unsustainable exploitation.